Analisis Kepuasan Penggunaan Aplikasi Classroom Pada Pembelajaran di Masa Pandemic Covid-19 menggunakan Metode Pieces - Nur Cahyono; Joy Nashar Utama Jaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
During the current Covid-19 Pandemic, there are many changes that occur in the learning process, the use of online learning media is currently widely used by all students in Indonesia. Media Knowledge Management System (KMS) is a must in every online learning. Online learning media is very much an option, one of which is google classroom. Google classroom is one of the most popular and used learning media. This study aims to find out the application of the google classroom as a learning media during the covid-19 pandemic, to analyze and know the level of google classroom user satisfaction by student of SMK Muhammadiyah 1 Balikpapan Information System in the learning process. This research uses PIECES framework method consisting of Performance, Informations and data, Economics, Control and security, Efficiency and Service. The results of this study obtained the average value of each domain, namely the Performance domain got a value of 4.037 (Satisfied), Informations and data got a value of 3.995 (Satisfied), Economics got a value of 3.958 (Satisfied), Control and security got a value of 3.866 (Satisfied) , Efficiency got a value of 3.855 (Satisfied) and Service got a value of 3.868 (Satisfied). Meanwhile, the total average level of satisfaction from all domains is 3.929 (Satisfied).